Endoscopic ultrasonography - Gress, Frank G.; Savides, Thomas J.; Ohio Library and Information Network (Hoboken, NJ : Wiley Blackwell, 2024)
"This text allows the learner to understand the history of EUS, the fundamentals of ultrasound, important references in EUS research, and how best to utilize EUS in diagnostic and interventional procedures. Experienced endosonographers can improve their therapeutic endoscopic skills. This fourth edition brings many new and exciting changes and additions to the book, especially new chapters dedicated to therapeutic procedures using lumen apposing metal stents. We have continued to emphasize a practical "how-to" approach to learning EUS"--
A History of Endoscopic Ultrasonography -- Basic principles and fundamentals of EUS imaging -- Learning EUS anatomy -- EUS instruments, room setup, and assistants -- EUS procedure consent and sedation -- The EUS report -- Endosonography of the mediastinum -- Linear-array EUS: normal anatomy -- High-frequency ultrasound probes -- EUS elastography -- Fundamentals of EUS FNA -- EUS FNA cytology : material preparation and interpretation -- EUS : applications in the mediastinum -- EUS for esophageal cancer -- EUS of the stomach and duodenum -- EUS for gastrointestinal subepithelial masses -- EUS and its emerging modalities for diagnosis and staging of pancreatic tumors -- EUS for pancreatic cysts -- The role of diagnostic EUS in inflammatory diseases of the pancreas -- Autoimmune pancreatitis -- EUS for biliary diseases -- EUS endohepatology in liver disease -- Colorectal EUS -- Therapeutic EUS for cancer treatment -- EUS-guided biliary access -- Pancreatic fluid collection drainage -- EUS-guided enteric anastomoses -- EUS guided drainage of pelvic fluid collections -- EUS hemostasis -- Training in EUS -- The future of EUS
Includes bibliographical references and index
Keywords: Endoscopic ultrasonography; Gastrointestinal system -- Diseases -- Diagnosis; Endosonography; Digestive System Diseases -- diagnostic imaging; Ultrasonography; Electronic books